2012
DOI: 10.1002/ange.201204705
|View full text |Cite
|
Sign up to set email alerts
|

Zwei ineinander umwandelbare Strukturen erklären die spektroskopischen Eigenschaften des Wasser oxidierenden Enzyms des Photosystems II im S2‐Zustand

Abstract: Aus der Kristallstruktur des Photosystems II abgeleitete DFT‐Modelle zeigen, dass der Sauerstoff produzierende Komplex im S2‐Zustand in zwei Formen existiert, die energetisch ähnlich und ineinander umwandelbar sind. Damit wird eine seit langem offene Frage zur Spektroskopie dieses Zustands beantwortet: Eine Form ergibt das Multilinien‐EPR‐Signal bei g=2.0 (rechts im Bild; rot O, violett Mn, gelb Ca), die andere das g≥4.1‐Signal (links).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 52 publications
2
14
0
1
Order By: Relevance
“…In the QM/MM optimized structures the spin ground-state for S 2 A corresponds to low spin (LS) S = 1/2 and for S 2 B corresponds to high spin (HS) S = 5/2, in agreement with previous results in the gas phase [11] (details concerning the broken symmetry states are described in Table S1). In particular we found that in S 2 A the LS (ground) state is 0.5 kcal mol À1 more stable than the HS state.…”
supporting
confidence: 88%
See 4 more Smart Citations
“…In the QM/MM optimized structures the spin ground-state for S 2 A corresponds to low spin (LS) S = 1/2 and for S 2 B corresponds to high spin (HS) S = 5/2, in agreement with previous results in the gas phase [11] (details concerning the broken symmetry states are described in Table S1). In particular we found that in S 2 A the LS (ground) state is 0.5 kcal mol À1 more stable than the HS state.…”
supporting
confidence: 88%
“…The endergonicity of the S 2 A to S 2 B transition and the height of the kinetic barrier between the two states have important consequences for the interpretation of previous experiments observing the transition between the EPR multi-line signal, associated with S 2 A , and the g % 4.1 signal, assigned to S 2 B . [11,15] According to our free-energy landscape, at room temperature (and in general for T ! 200 K) both S 2 A and S 2 B states are appreciably populated.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations